PERSUASIVE COMMUNICATION STRATEGIES IN HINDU KAHARINGAN RELIGIOUS COUNSELING: INTEGRATING TRADITIONAL AND DIGITAL VALUES IN BANTAI KARAU, AMPAH KOTA SUBDISTRICT, DUSUN TENGAH DISTRICT, EAST BARITO REGENCY - Evie; Akhmad Jaki; Sulandra; Desembeling; I Gusti Agung Dharmawan; Lidya Sinta Bela (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2025)
Religious diversity in Indonesia often presents challenges for local belief systems, including Hindu Kaharingan practiced by the Dayak community. Although integrated into the structure of Hinduism, its practices remain distinctive and deeply rooted in cultural values. Modernization and the rise of digital media have created a dilemma between preserving tradition and adapting to contemporary changes, making persuasive communication strategies essential for religious counseling to remain relevant, particularly for younger generations. This community service program employed the Asset-Based Community Development (ABCD) approach at Balai Basarah, Bantai Karau, East Barito Regency. The target groups included traditional leaders, religious counselors, youth, and Balai Basarah administrators. Data were collected through observation, in-depth interviews, and documentation, with triangulation applied to ensure validity. Findings reveal that Balai Basarah functions not only as a ritual space but also as a center for learning Kaharingan values. Persuasive communication strategies proved effective when integrating three key approaches: (1) psychodynamic, through the use of emotional narratives rooted in ancestral stories; (2) sociocultural, by reinforcing Dayak norms and cultural symbols; and (3) meaning construction, by simplifying messages supported with basic media such as leaflets and community-based online communication. Youth participation increased, particularly as the counseling was perceived to be more relevant and inclusive. This program demonstrates that tradition does not have to conflict with modernization, but can instead be strengthened through adaptive communication strategies grounded in local wisdom.